Research on Crack Propagation Behavior of Flexspline in Harmonic Reducer Based on XFEM - Xue Dongwen; Xu Yang; Xie Guosheng; Zhao Yanzheng; Liu Jihao (Jixie chuandong)
Fatigue cracking of the flexspline is an important cause of the decrease in accuracy and equipment reliability of the harmonic reducer. A model of harmonic reducer is taken as the research object, and an equivalent model of the flexspline is established based on the theory of shell moment to determine the parameters of stress concentration in the flexspline. Through finite element simulation, the location of the maximum stress node of the flexspline is obtained, and tiny angular cracks are introduced. By analyzing the crack tip stress field parameters, the ability and trend of the flexspline crack expansion are described. Based on the maximum principal stress damage evolution criterion, the differential behavior of crack expansion is simulated by the extended finite element method (XFEM), and an accelerated life experiment bench is built to verify the correctness of the extended finite element model. The results show that the crack expansion path matches with the finite element results; the stress concentration at the root of the flexspline teeth and the junction of the barrel and flange is prone to fatigue cracking most; the crack expansion path is affected by the incremental step and stress distribution； the stress distribution varies with the degree of crack expansion, causing a bias in the expansion path.